Cultural Revitalization through Innovation: Developing Kolotik as a Traditional Musical Instrument and Local Art Product in Indonesia - Frahma Ayudia Smarandhana; Jaeni; Yahfenel Evi Fussalam (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Objective: This study aims to analyze the innovation process in the development of the Kolotik musical instrument as a strategy for revitalizing traditional arts while strengthening Ciamis’s local art products. Method: A descriptive qualitative method with an arts ethnography approach was employed and conducted in Cimaragas District, Ciamis Regency, through participatory observation of the production and use of Kolotik, in-depth interviews with craftsmen, artists, community leaders, and arts educators, as well as visual documentation and field notes; data were analyzed through reduction, presentation, and conclusion drawing using source and technique triangulation. Results and Discussion: The findings indicate that Kolotik innovation occurs across four main domains: (1) the transformation of form and function through the development of size, color, and ornamentation, along with the expansion of functions from a traditional rhythmic instrument into an applied art product with aesthetic and economic value; (2) the development of numerical notation and simple scores as documentation media to transform oral transmission into more systematic learning, including applications to regional songs such as Bubuy Bulan and Manuk Dadali; (3) the strengthening of sustainability through the roles of community and educational institutions via training, performances, festivals, and the integration of arts learning based on local wisdom; and (4) the preservation of Kolotik’s cultural and philosophical values, such as harmony, togetherness, and human nature balance as a Sundanese identity that remains relevant amid the dynamics of modern society. Conclusion: Revitalization-based innovation enables Kolotik not only to endure as cultural heritage but also to evolve as an adaptive and functional learning instrument and local art product that sustainably reinforces Ciamis’s cultural identity.